E-SERVICE QUALITY ATTRIBUTES THAT INFLUENCES ONLINE PURCHASE INTENTION OF HARD LUXURIES AMONG GENERATION Y CONSUMERS IN MALAYSIA: THE MEDIATING ROLE OF E-SATISFACTION. - Shiranthi, Adris; Choo, Dennis, Ying Hoe (INTI International University, 2022)
Many department stores, jewellery and watch specialist stores closed due to the COVID-19 pandemic in 2020 and 2021. To sustain the revenue of these businesses many of these stores turn to e-commence. Research Problem: As Generation Y consumers’ in Malaysia represent a greater potential for these businesses, there was a lack of understanding of their online buying behaviour for Hard Jewellery especially during the early days of COVID19 pandemic. Research Objectives: (1)To study the relationship between the attributes for e-service quality and customer satisfaction of hard luxury online stores among Generation Y consumers; (2) To identify the relationship between customer e-satisfaction and online purchase intention of hard luxuries among Generation Y consumers and (3) To examine the mediating effect of customer e-satisfaction between attributes of e-service quality and the online purchase intention of hard luxuries among Generation Y consumers. The study was conducted on Generation Y customers consist of male and female Malaysians between 25 and 40 years old who had visited, purchased or used the services provided by hard luxury goods retailers online at least once; a pilot study was conducted prior the actual survey to test the validity and reliability of the research instrument; a convenient sample of 200 respondents was collected via a Google Form online questionnaire, where the link was shared on Facebook, WhatsApp and email, and MS Excel was used to sort the primary data. The data analysis was conducted with the help of Structural Equation Modeling (SEM) with partial least squares (PLS) analysis using the SmartPLS 3.0 software and SmartPLS was used to generate T-statistics for significance testing of both the inner and outer model. Result Outcomes: The study established that Website design, Customer Service and Fulfillment had an effect on customer e-satisfaction which had an effect on online purchase intention during the pandemic but security/privacy does not have a significant and positive effect on customer e-satisfaction and does not affect online purchase intention. Henceforth, customer e-satisfaction does not mediate the relationship between security/privacy and online purchase intention in the study.